The social representations of Covid-19 among primary health care' users in the Federal district, Brazil: A psychosocial approach. - Helena Eri Shimizu; Antonio Marcos Tosoli Gomes; Thémis Apostolidis (PLoS ONE)
Brazil was one of the countries most affected by the COVID-19 pandemic, including severe psycho-social effects. This study aimed to analyze the Federal District Primary Health Care users' Social Representations (SR) regarding Covid-19 through exploration of the elements that comprise their field, identification of the variations of their prominence, as well as analyze the relations and differences among them according to their socio-demographic characteristics and the participants' exposure to the disease. It was based on the Moscovici theory of social representations. 1,714 users from the Federal District Primary Health Units regions participated in the study: Central-South, North, West, Southwest, East and South. For the data collection, the free evocation technique was used. The data were analyzed by the Iramuteq software in the prototypical modality, analyzing similitude and analyzing x2 test of the most prominent words, considering the socio-demographic and Covid-19 exposure variables, establishing p < 0.05. It has been found that the social representations of the pandemic among the Federal District PHC' users formed a dyad: doctor and death. It was observed, however, that the doctor-death relationship was organized according to the vulnerabilities present in the face of the pandemic context and the affective-emotional aspects, the most excluded social segments experiencing the terrifying feelings caused by the virus, particularly the confrontation with death and its consequences, along with the absence of hope. In particular, it was evident that the representation of an absent or omissive State, due to the lack of protective measures for people already socially excluded, who demanded agile, more equitable policies, configured from the perspective of bioethics a moral debt on the part of the State to this population.